Antihyperlipidemic and renoprotective activities of methanolic extract of Canscora decussata extract in alloxan-induced diabetic rabbits (Bangladesh Journal of Pharmacology, 2013)
The current study was designed to evaluate the hypolipidemic and renopro-tective effects of methanolic extract of powdered Canscora decussata whole plant in the diabetic rabbits. Thirty rabbits were divided into five groups having 6 animals each including normal and diabetic controls groups, the remaining groups received methanolic extract in 400 and 600 mg/kg doses and another group got pioglitazone (3 mg/kg) for 30 days. Serum levels of triglycerides, total cholesterol, LDL-cholesterol, HDL-cholesterol, albumin, globulin and total proteins were estimated by using commercially available kits. The results showed that extract significantly (p